Clinical Case: Neurocognitive Evaluation in an Adult Patient with Wernickes Aphasia (Global Journal of Medical Research, 2020)
Wernicke's aphasia (AW) is a language disorder characterized by the inability to understand and repeat spoken language, the product of a lesion in an area of the left temporal lobe affecting the connection between the motor center and the sensory center. The objective of the present work is the cognitive evaluation of a 55-year-old adult patient with Wernicke's aphasia after asymptomatic ischemic event, with left Tempor-Parietal localization, through the neuropsychological and psychological consultation, clinical history and application of protocol for cognitive deterioration and Boston Test for diagnosis of Aphasia. identify areas and skills affected and conserved, which will direct the rehabilitation process in the future.
Keywords: cognitive profile aphasia of wernicke temporo-parietal left cognitive impairment